Essays on services offshoring - Magli, Martina (2019)
This thesis provides a comprehensive description of trends and patterns in trade in services, and then proceeds to an in-depth analysis of the average and distributional effects of services offshoring -- defined as the imports of intermediate services from abroad -- on local labour markets. The first essay (chapter 2) is an extended introduction to trade in services and to the unique dataset used in the remainder of the thesis. The second and third essays (chapters 3 and 4 respectively) are dedicated to the empirical study of changes in employment levels and wages in those local labour markets from where the offshoring of services originates.Differently from the rest of the literature, the analysis takes into account both the direct effects (on the firms importing services), and the indirect effects (e.g. imitation, supply chain effect, change in competition) of services offshoring.